Trust behaviour of sexual minorities: Evidence from a large-scale trust game experiment - Francesco Berlingieri; Matija Kovacic; Elena Stepanova (Global Labor Organization (GLO), 2025)
Using a large-scale incentivized trust game experiment conducted across all 27 EU member states, we find that sexual minorities exhibit greater prosocial behaviour toward another vulnerable group but not toward an unknown counterpart, compared to heterosexual individuals. The observed effects are both relationship- and context-specific. Specifically, bisexual individuals and those identifying with a sexual orientation other than lesbian, gay, or heterosexual demonstrate higher trusting behaviour toward counterparts who frequently experience loneliness. This effect is not attributable to higher expectations of return, differences in risk preferences, or the individual's own loneliness status. Furthermore, we find evidence that this relationship-specific prosocial behaviour among sexual minorities is more pronounced in countries with lower levels of LGBTIQ+ rights protection, suggesting that it is heightened in contexts where minorities face a greater risk of exclusion or discrimination. We do not find statistically significant differences in overall trustworthiness across sexual orientations. However, the results offer some evidence that bisexual individuals are more trustworthy than heterosexual trustees when they feel a strong connection to their counterpart.
Keywords: C91; C71; D64; J15; H80; 330; Trust game; pro-sociality; LGBTIQ+; loneliness